Algorithmic Differentiation of Parenting Phenotypes: Clustering Parental Burnout, Psychological Flexibility, and Their Effects on Child Effortful Control - Paredes, Laura; Mejía, Andrés (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to differentiate parenting phenotypes via algorithmic clustering of parental burnout and psychological flexibility, and to examine their subsequent impact on child effortful control. Methods and Materials: A cross-sectional, quantitative study was conducted with primary caregivers of children aged to years in Colombia. Data were collected via a secure online survey utilizing validated instruments: the Parental Burnout Assessment (PBA), the Parental Acceptance and Action Questionnaire (PAAQ; reverse-coded), and the Effortful Control scale from the parent-reported Child Behavior Questionnaire (CBQ). A two-step cluster analysis (hierarchical with Ward’s method followed by K-means) was applied to standardized -scores of the PBA and PAAQ to determine parenting profiles. Group distinctiveness and effects on child effortful control were analyzed using MANOVA and ANCOVA, controlling for parent age and child gender, followed by post-hoc Tukey’s HSD tests. Findings: The clustering algorithm yielded an optimal three-phenotype solution (average silhouette width = ): Adaptive ( , low burnout, high flexibility), Strained ( , high burnout, low flexibility), and Vulnerable ( , moderate scores). A MANOVA confirmed significant multivariate distinctiveness between the clusters (Wilks’ , , , ). ANCOVA revealed a significant main effect of parenting phenotype on child effortful control ( , , ). Children of the Adaptive Phenotype exhibited the highest effortful control ( ), scoring significantly higher than both the Vulnerable ( ) and Strained ( ) phenotypes ( for all pairwise comparisons). Conclusion: Distinct algorithmic parenting phenotypes significantly predict variations in child effortful control, highlighting the critical influence of parental psychological states on child self-regulation.